FACING THE NEW TIMES OF JUVENILE SOCIAL-CRIMINAL ACTION - Méndez Navarro, Luz Marina (2019)
This article focuses on the description and analysis of data offered by the INE (National Statistics Institute of Spain), the collection of court judgments and the data obtained through the realization of life stories, to minors who at that time, were complying with judicial measures, in order to provide solutions to juvenile crime changes for its reduction. The sample is the following: 25 adolescents who were complying with judicial measures in an open environment; the analysis of 132 sentences, and statistical tables of the INE from the year 2013 to the most recent, 2016.